The Influences of NH4F-HF System on Dental Minerals - Jong, Mi-Hyang; Rim, Ki Ho; Hong, Un-sung; Ro, Myong-Sung; Son, Man-Bok; Kim, Sang-Jun (Medical Science Journal for Advance Research, 2026)
Aim: The influence of NH4F-HF system on the fluoride-dental minerals reaction system was investigated. Methods: Fluoride solutions with a fluoride concentration of 1.23% each were used: 1.23% NaF-H3PO4-HF(APF, pH 2.1), 1.23% NH4F-HNO3 (pH 3.6), and 1.23% NH4F-HF (pH 3.6). Fluoride solutions prepared above were diluted 10 times and used as 0.123% fluoride solutions. 300mg of Hydroxyapatite (HA:Ca10(PO4)6(OH)2) was deposited for 20min by adding 40mL of each of 1.23% fluoride solutions. In the same way, 300mg of calcium hydrogen phosphate (CaHPO4·2H2O) was deposited for 20min by adding 40mL of each of 0.123% fluoride solutions. The HA and CaHPO4·2H2O were added to the different fluoride solutions and deposited. Each reaction was performed 3 times, respectively. Three reaction samples for each fluoride were mixed, filtered, washed, centrifuged and dried as reaction samples. The reaction products were identified and the content of calcium fluoride was determined by X-ray diffraction. Results: The highest CaF2 content was found in the HA sample treated by 1.23% NH4F-HF(pH 3.6) solution, while it was almost absent in the sample treated by NaF. In addition, the highest CaF2 content was found in the calcium hydrogen phosphate sample treated by 0.123% NH4F-HF(pH 3.6) solution. Conclusion: The chemical reactivity of ammonium fluoride solution increases with increasing added HF content.